Candice Lin - a hard white body - Arndt, Lotte 1979-; Umolu, Yesomi (The University of Chicago Press, 2019)
This publication showcases A Hard White Body, an evolving project by Candice Lin presented at Bétonsalon -Centre d'art et de recherche, Paris; at Portikus, Frankfurt/Main; and at the Reva and David Logan Center for the Arts, University of Chicago. A Hard White Body weaves together material and nonhuman histories alongside the life and work of three historical figures: American writer James Baldwin (1924-1987); French explorer and global traveler Jeanne Baret (1740-1807); and artist and naturalist Maria Sibylla Merian (1647-1717). Lin uses porcelain, a material whose history includes nineteenth-century imperial and scientific uses, to highlight fantasies surrounding whiteness and purity, only to subject her porcelain assemblages to pungent organic materials. She thus stages processes of contamination between organic and inorganic materials, creating an unstable sculptural ecosystem. In addition to an essay by curator Lotte Arndt that discusses the various iterations of Lin's project, the publication features an essay by Rizvana Bradley; a conversation between Jih-Fei Cheng and Mel Y. Chen; and a conversation between the artist and C. Riley Snorton. These texts are accompanied by a visual essay by the artist and a selection of exhibition views.00Exhibition: Bétonsalon -Centre d'art et de recherche, Paris (06.09-23.12.2017); Portikus, Frankfurt/Main (10.02-08.04.2018); Reva and David Logan Center for the Arts, University of Chicago 14.09-28.10.2018)
"This publication was produced in conjunction with the exhibitions Hard White Body/Un Corps Blanc Exquis (September 6-December 23, 2017), curated by Lotte Arndt and Lucas Morin and organized by Bétonsalon - Center for Art and Research & Villa Vassilieff, Paris ; A Hard White Body, a Soft White Worm (February 10-April 8, 2018), curated by Lotte Arndt, Lucas Morin and Philippe Pirotte and organized by Portikus, Frankfurt am Main ; and A Hard White Body, Porous Slip (September 14-October 28, 2018), curated by Yesomi Umolu and organized by Logan Center Exhibitions at the Reva and David Logan Center for the Arts at the University of Chicago."
Keywords: Lin, Candice -- 1979-; Ausstellungskatalog -- Bétonsalon - Center for Art and Research & Villa Vassilieff -- 06.09.2017-23.12.2017 -- Paris; Ausstellungskatalog -- Portikus -- 10.02.2018-08.04.2018 -- Frankfurt am Main; Ausstellungskatalog -- Reva and David Logan Center for the Arts -- 14.09.2018-28.10.2018 -- Chicago, Ill; Bildband